The year of living biblically : one man's humble quest to follow the Bible as literally as possible - Jacobs, A. J., 1968- (New York : Simon & Schuster, 2007)
Raised in a secular family but interested in the relevance of faith in our modern world, A.J. Jacobs decides to attempt to obey the Bible as literally as possible for one full year. He vows to follow the Ten Commandments. To be fruitful and multiply. To love his neighbor. But also to obey the hundreds of less publicized rules: to avoid wearing clothes made of mixed fibers; to stone adulterers. The resulting spiritual journey is at once funny and profound, reverent and irreverent, personal and universal and will make you see history's most influential book with new eyes. Jacobs embeds himself in a cross-section of communities that take the Bible literally: he tours a creationist museum and sings hymns with Amish; he dances with Hasidic Jews and does Scripture study with Jehovah's Witnesses. He wrestles with seemingly archaic rules that baffle the 21st-century brain, and he discovers ancient wisdom of startling relevance.--From publisher description.
Includes bibliographical references (p. [343]-348) and index.
Keywords: Bible -- Criticism, interpretation, etc